Quantification of Antimalarial Quassinoids Neosergeolide and Isobrucein B in Stem and Root Infusions of Picrolemma sprucei Hook F. by HPLC-UV Analysis - Nunomura, Rita C. S.; Silva, Ellen C. C.; Nunomura, Sergio M.; Amaral, Ana C. F.; Barreto, Alaíde S.; Siani, Antonio C.; Pohlit, Adrian M. (IntechOpen, 2012)
None